Hybridization between two sister species of Bromeliaceae: Vriesea carinata and V. incurvata. (23rd June 2016) - Zanella, Camila M.; Palma-Silva, Clarisse; Goetze, Márcia; Bered, Fernanda
Abstract: Studies on interspecific gene flow and hybridization are important for understanding speciation processes and the movement of genes across species boundaries. In sympatric areas, hybridization between closely related species can be a common phenomenon and the degree of reproductive isolation (RI) among these species is closely related to the probability of hybrid formation. Here, using 14 nuclear microsatellites and two plastid DNA regions, we investigated the occurrence of natural hybridization in four sympatric populations of Vriesea carinata and V. incurvata . We also analysed four allopatric populations (two from each species), totalling 272 samples. These species share pollinators and have sequential flowering with a short period of overlap. Based on genetic assignment tests, 17 hybrids were detected in two of the four sympatric populations studied (8.29% of the individuals sampled). Our results showed low levels of nuclear ( F ST = 0.098) and high plastid genetic differentiation ( F ST = 0.601), with no haplotype sharing between parental species. The presence of plastid DNA haplotypes of both parental species in the hybrids indicated that hybridization probably occurred in both directions. We identified few hybrids, probably in consequence of some degree of RI between these species. Several RI barriers may be acting to maintain species integrity, temporal flowering differences being one important factor.